32nd AIAA Applied Aerodynamics Conference 2014
DOI: 10.2514/6.2014-2562
|View full text |Cite
|
Sign up to set email alerts
|

Control of Unsteady Aerodynamic Loads Using Adaptive Blowing

Abstract: Adaptive slot blowing was experimentally investigated on a NACA 0018 airfoil model as a method to minimize unsteady aerodynamic loads. Tests were conducted in a wind tunnel facility specifically designed to facilitate high amplitude wind speed fluctuations. Initially, the effect of steady blowing from a control slot located near the leading-edge was investigated under quasistatic conditions. At Reynolds numbers ranging from 1.5·10 5 to 5·10 5 , a relative change in lift of ∆cl ≈ 0.5 was obtained over a wide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Moreover, load alleviation induced by a suction or pulsed-blowing coupled mechanism [266] is attributable to boundarylayer extraction (suction) and energizing (blowing), unsteady shear-layer excitation, thrust generation and streamwise vortices. Adaptive blowing (regulated steady blowing) was also credited with load-excursion elimination, by controlling boundary-layer separation using jet-momentum flux [267], with a successful demonstration of the eradication of dynamic-stall vortex using jet momentum under deep stall conditions. Next, dynamic blowing was also successfully applied for lift-excursions and dynamic-stall suppression, to achieve nearly constant phase-averaged lift or mitigated unsteady-aerodynamic loads [268], whereas passive adaptive blowing may be ideal for load alleviation and reduced blade-root bending and tip deflections [269]; mainly, this self-regulatory mechanism is governed by pressure-differential feedback obtained from control-ports on either side of the aerofoil/blade.…”
Section: Blowing-suction Controlmentioning
confidence: 99%
“…Moreover, load alleviation induced by a suction or pulsed-blowing coupled mechanism [266] is attributable to boundarylayer extraction (suction) and energizing (blowing), unsteady shear-layer excitation, thrust generation and streamwise vortices. Adaptive blowing (regulated steady blowing) was also credited with load-excursion elimination, by controlling boundary-layer separation using jet-momentum flux [267], with a successful demonstration of the eradication of dynamic-stall vortex using jet momentum under deep stall conditions. Next, dynamic blowing was also successfully applied for lift-excursions and dynamic-stall suppression, to achieve nearly constant phase-averaged lift or mitigated unsteady-aerodynamic loads [268], whereas passive adaptive blowing may be ideal for load alleviation and reduced blade-root bending and tip deflections [269]; mainly, this self-regulatory mechanism is governed by pressure-differential feedback obtained from control-ports on either side of the aerofoil/blade.…”
Section: Blowing-suction Controlmentioning
confidence: 99%
“…The time delay became more significant with increasing angles of attack because of more separated flow. The effects of the slot blowing on unsteady aerodynamic load control with a freestream velocity from 6.7 m/s to 22.2 m/s on NACA0018 aerofoil was experimentally evaluated by Mueller-Vahl et al [94]. The results showed that the lift oscillation due to the unsteady incoming flow can be effectively counteracted by dynamically adapting the slot blowing velocity.…”
Section: Surface Jet Blowingmentioning
confidence: 99%
“…Neunaber and Braud create an inversed EOG by rotating a bar into the inflow field of a wind tunnel 15 . Other two‐dimensional studies show load alleviation potential by active blowing 16 or trailing edge flaps, 17 yet they do not target extreme loads specifically.…”
Section: Introductionmentioning
confidence: 99%